An Overview of the Paris Hills Phosphate Project, South-Eastern Idaho - Kenneth L. Norris (Canadian Institute of Mining, Metallurgy and Petroleum, 2011)
Stonegate Agricom Ltd. is currently conducting exploration and development drilling of the Paris Hills Phosphate Project (Paris Hills Project) located in Bear Lake County, southeastern Idaho, 3.2 km west of the towns of Paris and Bloomington, Idaho. The project is located adjacent to a highway and 19 km by paved highway to Montpelier, Idaho where the Union Pacific Railroad system is located. Power and water are available locally. The nearest metropolitan centre is Salt Lake City, Utah approximately 225 km by road to the south-west of the property. The Paris Hills Project encompasses an area of approximately 856 hectares. Property holdings consist of three (3) patented lode mining claims and 16 contiguous fee parcels (some with federal phosphate leases). Active open pit phosphate mining operations are located in surrounding counties in south-east Idaho and are owned and operated by Agrium Inc., Monsanto Company and J.R. Simplot Company. The Paris Hills Project is located near the centre of the Western Phosphate Field which constitutes the most extensive phosphorite beds in the United States. Phosphate beds of the Western Phosphate Field occur within the Phosphoria Formation of Permian age and extend over an area of more than 350,000 km2 including extensive areas of Idaho, Utah, Wyoming and Montana. At Paris Hills the phosphate mineralized beds occur in the overturned limb and the horizontal limb of the Paris Syncline. Grades and thicknesses in both the western overturned limb and the eastern horizontal limb of the anticline are similar. The vast majority of potential mineralization occurs in the horizontal limb which underlies most of the property holdings. Mineralization in the overturned limb has a strike length of over three (3) kilometres and extends from the surface to a depth exceeding 300 m depending on location along the north-trending strike of outcrops. Depths of the horizontal limb range from surface along the north side of Bloomington Canyon to estimated depths of 915 to 1,035 m at Paris Canyon. The property contains an Inferred resource of 109.6 million tonnes at 23.6% P2O5 over two mineralized horizons. The phosphate zones have a strike length of over 3 km and extend from surface to a depth of at least 900 m. Drilling commenced late in the 3rd quarter of 2010 and is planned to continue through 2011. The drilling was planned to target an area of potentially higher grade phosphate mineralization and better define and upgrade the current resources.